2018
DOI: 10.1111/jvim.15302
|View full text |Cite
|
Sign up to set email alerts
|

Equine asthma: Integrative biologic relevance of a recently proposed nomenclature

Abstract: The term “equine asthma” has been proposed as a unifying descriptor of inflammatory airway disease (IAD), recurrent airway obstruction (RAO), and summer pasture‐associated obstructive airway disease. Whilst the term will increase comprehensibility for both the lay and scientific communities, its biologic relevance must be compared and contrasted to asthma in human medicine, recognizing the limited availability of peer‐reviewed equine‐derived data, which are largely restricted to clinical signs, measures of air… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
98
1
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 81 publications
(102 citation statements)
references
References 114 publications
(151 reference statements)
0
98
1
3
Order By: Relevance
“…This tendency toward a younger age of onset parallels the development of asthma in humans, most commonly a childhood disease where the allergic or hypersensitivity response is related to specific development of neonatal and juvenile immunity 21‐23 . In neonatal murine models of asthma, increased diversity of lung or gut microbiota promotes a more favorable environment for tolerance against allergic disease by inducing T‐regulatory cells, lower concentrations of IgE and altered balance of Th1/Th2 immune responses 24‐26 . In studies of cats, a similar relationship has been suggested between gut and lung mucosal microbiomes 27,28 .…”
Section: Discussionmentioning
confidence: 83%
“…This tendency toward a younger age of onset parallels the development of asthma in humans, most commonly a childhood disease where the allergic or hypersensitivity response is related to specific development of neonatal and juvenile immunity 21‐23 . In neonatal murine models of asthma, increased diversity of lung or gut microbiota promotes a more favorable environment for tolerance against allergic disease by inducing T‐regulatory cells, lower concentrations of IgE and altered balance of Th1/Th2 immune responses 24‐26 . In studies of cats, a similar relationship has been suggested between gut and lung mucosal microbiomes 27,28 .…”
Section: Discussionmentioning
confidence: 83%
“…Asthma in horses is characterized by reversible bronchospasm and airway inflammation upon exposure to inhaled antigens. It is a complex disease that includes individual susceptibility to allergen exposure, variable levels of severity, and different inflammatory phenotypes . Exacerbations are characterized by the presence of clinical signs and are mainly triggered by exposure to aerosolized allergens found in hay and bedding, including fungal particles, mites, and endotoxin .…”
Section: Introductionmentioning
confidence: 99%
“…Mild asthma in horses is a commonly occurring inflammatory airway disease, which provides a biologically appropriate model for allergic and nonallergic phenotypes of asthma in humans . It is a naturally occurring disease that, similar to asthma in humans, likely is triggered by a combination of pathophysiological mechanisms.…”
Section: Introductionmentioning
confidence: 99%